The role of media in achieving SDGs: The Media's Vital Role in SDG Success - Javed, Asma (Journal of Peace, Development and Communication, 2024)
“If information and knowledge are central to democracy, they are the conditions for development. It is that simple” –Kofi Annan, former UN Secretary General. This research paper investigates the multifaceted role of media in advancing the agenda of the Sustainable Development Goals achieving them by 2030.Media platforms wield substantial influence in shaping public opinion, driving policy changes, and fostering global collaboration. The paper examines how media serves as a catalyst for raising awareness about the SDGs. This study delves into the advocacy role and holds stakeholders accountable for their commitments to the SDGs. Through agenda-setting, the media prioritizes issues pertinent to sustainable development, shaping public discourse and influencing decision-makers at local, national, and international levels. This research elucidates how media cultivates inclusive approaches to sustainable development integrated into policy frameworks. Finally through a comprehensive analysis this paper underscores the importance of media in mobilizing resources, forging partnerships, and galvanizing collective action towards the realization of the SDGs by 2030.